2017
DOI: 10.1155/2017/8181743
|View full text |Cite
|
Sign up to set email alerts
|

Tendon-Sheath Mechanisms in Flexible Membrane Wing Mini-UAVs: Control and Performance

Abstract: Flexible membrane wings (FMWs) are known for two inherent advantages, that is, adaptability to gusty airflow as the wings can flex according to the gust load to reduce the effective angle of attack and the ability to be folded for compact storage purposes. However, the maneuverability of UAV with FMWs is rather limited as it is impossible to install conventional ailerons. The maneuver relies only on the rudders. Some applications utilize torque rods to warp the wings, but this approach makes the FMW become unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Though these are the four common types of UAVs, there is a unique type of UAV called the Flexible Membrane Wing (FMW) UAV [10]. The FMW has wings made from flexible membrane material, with the advantages of this being easy of storage (as the wings can simply be folded up) and better control and maneuverability in windy conditions (as the flexible wings dynamically adjust to cater for wind preventing "adaptive washout").…”
Section: Autonomous Vehiclesmentioning
confidence: 99%
“…Though these are the four common types of UAVs, there is a unique type of UAV called the Flexible Membrane Wing (FMW) UAV [10]. The FMW has wings made from flexible membrane material, with the advantages of this being easy of storage (as the wings can simply be folded up) and better control and maneuverability in windy conditions (as the flexible wings dynamically adjust to cater for wind preventing "adaptive washout").…”
Section: Autonomous Vehiclesmentioning
confidence: 99%
“…Its flight safety is threatened by the complex near-ground environment and unpredictable air flow conditions. Its frequent crash incidents indicate that the traditional flight control strategies designed for a conventional large aircraft are not suitable for SUAV's flight control due to its low-speed, lightweight, coarse sensor, and low-cost actuator [2].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers and engineers propose hundreds of methods to improve an SUAV's flight performance [2][3][4]. Some researchers get their inspirations from the nature, such as flying creatures like birds and insects which are capable of high-performance flight.…”
Section: Introductionmentioning
confidence: 99%
“…If the pre-tension is significantly varying, the model will change extensively and thus rendering the feed-forward control not as effective. To investigate this issue, an adaptive backstepping controller has been implemented to the TSM actuated wing warping system in [97]. In that study, it was found that the adaptive backstepping controller performs well and is more robust than the feed-forward controller.…”
Section: Discussionmentioning
confidence: 99%